2015
DOI: 10.2147/ppa.s78495
|View full text |Cite
|
Sign up to set email alerts
|

Information and decision-making needs among people with affective disorders – results of an online survey

Abstract: BackgroundPatient decision aids are one possibility for enabling and encouraging patients to participate in medical decisions.ObjectiveThis paper aims to describe patients’ information and decision-making needs as a prerequisite for the development of high-quality, web-based patient decision aids for affective disorders.DesignWe conducted an online cross-sectional survey by using a self-administered questionnaire including items on Internet use, online health information needs, role in decision making, and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 36 publications
1
45
0
1
Order By: Relevance
“…Three interesting categories ‘being the underdog’, ‘being controlled’, ‘being omitted’ described consumers’ experiences of involvement (Dahlqvist Jönsson et al, ). Most consumers experienced lower involvement than they expected (De las Cuevas, Peñate, et al, ; Liebherz et al, ). Additionally, consumers also felt excluded from decisions about their physical health which they considered as important as mental health (Ehrlich & Dannapfel, ; Small et al, ).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Three interesting categories ‘being the underdog’, ‘being controlled’, ‘being omitted’ described consumers’ experiences of involvement (Dahlqvist Jönsson et al, ). Most consumers experienced lower involvement than they expected (De las Cuevas, Peñate, et al, ; Liebherz et al, ). Additionally, consumers also felt excluded from decisions about their physical health which they considered as important as mental health (Ehrlich & Dannapfel, ; Small et al, ).…”
Section: Resultsmentioning
confidence: 90%
“…the diagnosis of illness) (De las Cuevas & Peñate, ; De las Cuevas, Peñate, et al, ; Park et al, ). In studies reporting SDM as a single dimensional concept, most consumers preferred SDM, and a minority of them preferred passive involvement (Cosh et al, ; De las Cuevas & Peñate, ; De las Cuevas, Peñate, et al, ; Ehrlich & Dannapfel, ; Liebherz et al, ; Nott, Mcintosh, Taube, & Taylor, ). Specifically, three articles reported that consumers also preferred shared involvement in physical health (Ehrlich & Dannapfel, ; Small et al, ; Wright‐Berryman & Kim, ; Wright‐Berryman & Cremering ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many treatments for depression have demonstrated efficacy, including medications, psychotherapy, electroconvulsive therapy, deep brain stimulation, and complementary and alternative medicine options. Individuals living with depression have rated decisions about medication use as one of the top three most difficult treatment decisions they make (Liebherz, Tlach, Härter, & Dirmaier, ).…”
Section: Introductionmentioning
confidence: 99%